Numerical Simulation of Droplet Behavior under Varying Density Ratios Using Finite Volume-Front Tracking Method - Kurniawan, Dondi; Yoanita, Yulia Venti; Pinindriya , Sinung Tirtha; Eli Kumolosari; Angga Darma Prabowo; M. Rangga Saputra (International Journal of Aviation Science and Engineering - AVIA, 2024)
The study of droplet dynamics is very important to understand the mechanism of heat, mass, and momentum transfer in two phases. One approach to studying this phenomenon is through numerical simulation. The front tracking method is one of the techniques often used in numerical simulation of droplets to handle phase interactions in multiphase flows. This study aims to study the characteristics of droplets when they collide with surfaces with varying density values. The modeling used in this study is an interface diffusion approach using 2 types of fluids that have different properties. The domain used is Square Box-Staggered Grid. The software used is MATLAB R2024a. The results of the study indicate that the density ratio has a significant effect on the spreading factor, apex height, spreading velocity and pressure.